Effect of prior instructions on preprogrammed reactions of trunk muscles in individuals with and without chronic low back pain - Shenoy, Sh.; Balachander, H.; Sandhu, J.S. (Нейрофизиология, 2014)
The late component of the stretch reflex occurring in humans within a 40 to 120 msec interval following a loading perturbation is qualified as a preprogrammed muscle reaction (PPR). The PPR size can be significantly modulated with prior instructions. These modifications are significantly influenced by a number of factors, in particular by the presence of pain syndromes. The objective of our study was to compare the effect of prior instructions on the PPR amplitude in the trunk muscles in individuals with chronic low back pain (LBP) compared to healthy controls. LBP is a widespread syndrome, especially in athletes. Surface EMGs were recorded from superficial trunk muscles, rectus abdominis (RA) and erector spinae (ES), in athletes suffering from chronic LBP (n = 24) and asymptomatic (healthy) athletes (n = 25). Loading perturbations (induced by dropping a weight, application of 3 kg force, ≈ 30 N, to the outstretched hand from a 8 cm height) were introduced in standing at a known time with prior instructions to “let go” for the induced perturbation or to “resist” it. The root mean square (RMS) of the EMG amplitudes within the reaction duration were compared between the two groups. Statistically significant differences were obtained when the mean PPR EMG amplitudes were compared between the LBP and control groups for the above two task instructions; this was found for both examined muscles, RA and ES (P < 0.05). Therefore, individuals with chronic LBP exhibit poorly modulated PPR amplitudes according to prior task instructions. Changes in the networks controlling automatically regulated movements and excitability of the spinal pathways could be responsible for this specificity